Sex Differences in Functional Stress Test Versus CT Angiography in Symptomatic Patients With Suspected CAD: Insights From PROMISE - Pagidipati, Neha J. (J Am Coll Cardiol, 2016)
BACKGROUND: Risk stratification is an important goal of cardiac noninvasive tests (NITs), yet little contemporary data exist on the prognostic value of different NITs by patient sex. OBJECTIVES: To compare the results and prognostic information derived from anatomic versus stress testing in stable men and women with suspected coronary artery disease. METHODS: In 8966 PROMISE trial patients tested as randomized (4500 computed tomographic angiography [CTA], 52% female; 4466 stress testing, 53% female), we assessed the relationship between sex and NIT results using logistic regression, and the relationship between sex and a composite of death, myocardial infarction, and unstable angina hospitalization using Cox proportional hazards models. RESULTS: In women, a positive CTA (≥70% stenosis) was less likely than a positive stress test (8% vs. 12%, adjusted OR 0.67 [95% CI 0.55-0.82]). Compared with negative tests, a positive CTA was more strongly associated with subsequent clinical events than a positive stress test (CTA adjusted HR 5.86 [95% CI 3.32-10.35]; stress adjusted HR 2.27 [95% CI 1.21-4.25]; adjusted p=0.028). Men were more likely to have a positive CTA than stress test (16% vs. 14%, adjusted OR 1.23 [95% CI 1.04-1.47]). Compared with negative tests, a positive CTA was less strongly associated with subsequent clinical events than a positive stress test in men, although this difference was not statistically significant (CTA adjusted HR 2.80 [95% CI 1.76-4.45]; stress adjusted HR 4.42 [95% CI 2.77-7.07]; adjusted p=0.168). Negative CTA and stress tests were equally likely to predict an event in both sexes (adjusted p-values=NS). A significant interaction between sex, NIT type, and test result (p=0.01) suggests that sex and NIT type jointly influence the relationship between test result and clinical events. CONCLUSIONS: The prognostic value of an NIT result varies by test type and patient sex. Women appear to derive more prognostic information from a CTA, while men tend to derive similar prognostic value from both test types.